Phenomenon Game Online as Social Pathology in the Community Teenager : Case Study of Seumara Village, Pante Ceureumen District West Aceh Regency - Satri Satri (Seutia Hukamaa Cendekia, 2023)
The rise of online games, which are popular among teenagers, is due to the development of the era of globalization and increasingly sophisticated technological developments, which have a negative impact on teenagers. The author is interested in research by raising the title of the online gaming phenomenon as a social pathology among teenagers in Seumara Gampong, Pante Ceureumen District, West Aceh Regency. This research uses a mixed method, collecting data through observation, questionnaires, interviews, and documentation. The results of the study from distributing questionnaires to 19 teenagers, 15 teenagers (78.9%) said that online games are a social pathology because online games have a negative impact on academic achievement, aggressive behavior, dirty talk, neglecting prayers, and ignoring parental orders. Meanwhile, 4 teenagers (21.1%) said that online games are not a social pathology because playing online games can train hand and eye speed and become a profession to make money. The results of interviews from the gampong government, officials, community leaders, Imum Chik, and parents of teenagers said that the gampong government and parents had tried to overcome the online gaming phenomenon among teenagers by providing advice and warnings. The gampong government and parents continue to supervise/control teenagers so that they do not become addicted to playing online games. The gampong government has provided warnings and guidance to teenagers to use their free time usefully